In vitro Antibacterial Activity of Medicinal Plants of Nepal: A Comprehensive Review - Pandey, Rupa; Pradhan, Prasil; Shrestha, Kusum; Adhikari, Sanjib; Rijal, Komal Raj; Poudel, Pramod; Ghimire, Prakash; Sharma, Supriya (Journal of Nepal Biotechnology Association, 2026)
Antimicrobial resistance is a growing challenge in medicine. Medicinal plants are used as antibiotic medicines for primary healthcare. This review systematically compiled and analyzed published in vitro studies on the antibacterial activity of medicinal plants of Nepal. A comprehensive search on PubMed, NepJOL and Google Scholar identified 27 original studies in Nepal, approximately 120 plant species from 100 genera and over 50 families. Leaves were most frequently tested (66.7%), followed by roots/rhizomes (40.7%), fruits/seeds/flowers (33.3%), bark (22.2%), and whole plant (18.5%). Methanol (51.9%) and ethanol (33.3%) were commonly used extraction solvents, with cold maceration being predominant method. Plant extracts demonstrated activity against both Gram-positive and Gram-negative bacteria, with Gram-positive strains generally more susceptible (~70% of studies). The largest ZOI reported was 31 mm for an ethyl acetate extract of Terminalia bellirica fruit against Pseudomonas aeruginosa. MIC values ranged from tens to several hundred µg/ml. However, methodological heterogeneity, limited MIC/MBC reporting and under-representation of multidrug-resistant bacteria highlight the need for standardized and reproducible studies to identify promising species for antibacterial drug development.